The Legal Status of the Principle of Non-Intervention - A. Guerreiro (Московский журнал международного права, 2022)
INTRODUCTION. Te United Nations framework reﬂects the need for a paradigm shif in order to assure that the unilateral use of sovereign powers will no longer be a threat for the humankind like until 1945. Tus, the new world order highly contributed to the crystallisation of certain principles and since then States have been taking advantage of the UN system to consolidate and develop the principle of non-intervention. Tis paper seeks to identify and critically explore the evolution of intervention in the United Nations bodies since 1945 and subject the fndings to the criteria adopted by the ILC in its 2019 draf conclusions on peremptory norms of general international law (jus cogens) in order to determine if intervention has reached the status of jus cogens norm.MATERIALS AND METHODS. Tis work begins with the identifcation of the elements comprising the principle of non-intervention from the Charter of the United Nations followed by the description of the criteria established by the ILC to recognise the existence of a peremptory norm of general international law. Subsequently, will be developed an examination of the present State practice, the rulings of the ICJ more relevant for the matter in hand and this will be followed by a comprehensive analysis to the resolutions adopted by the UNSC and the UNGA which are decisive to determine in the end that the prohibition of non-intervention is a peremptory norm of international general law. Tis study is developed within the framework of international law and is based on open sources, as well as legal doctrine and normative elements.RESEARCH RESULTS. Te result of the research brings the notion that the beginning of a new era afer the end of World War II came as a result of the global awareness of the dangers of unilateralism and absolute sovereignty for humankind. Te principle of nonintervention is accepted as part of customary international law and the activities taken in the framework of the UN over the last almost eight decades show how States wanted to shape the scope of this principle.DISCUSSION AND CONCLUSIONS. Considering all the eﬀorts invested by States in the attempts to reach a notion of non-intervention supported by the majority of the humankind, such principle is not only recognised as having a customary nature, but it also entails concrete rights and duties for States. In theend, the singular importance given to the principle of non-intervention leads to the conclusion that from it derives a prohibition of intervention corresponding to a jus cogens norm.